Impact Of Social Support, Psychological Capital, And Workplace Spirituality To Employee Engagement At Company - Alviyanti Herlina; Abdul Mujib (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
All companies expect their employees better in terms of work performance, able to adapt to changes inEmployee engagement, Social Support, Modal Psychologis, Workplace, Spiritualitythe working environment, able to adapt the organizational culture so that employees are able tocommit the company to achieve its goals. In other words, companies need a lot of employees are tiedto the company.This study was conducted to determine the effect of social support, psychologicalcapital, and workplace spirituality to the company's employee engagement. The total population of280 employees of PT Tunas Jaya Makmur Abadi and sampled 266 employees of production takenusing purposive sampling technique.The results showed that the four dimensions of social support (areal support, information support, emotional support, and implicit support) not significant effect onemployee engagement, three-dimensional psychological capital (self-efficacy, optimism, andresilience), two dimensions of workplace spirituality (inner life and belonging to a community) thatsignificantly influence employee engagement. Researchers hope the implications of this study can bereviewed and could be developed in future studies. For example, by adding other variables related toemployee engagement that may have a bigger impact on employee engagement. DOI: 10.15408/tazkiya.v22i1.8151